Kebijakan Pemerintah Daerah Kota Depok Terhadap Penanggulangan Anak Putus Sekolah Berdasarkan Pasal 19 Peraturan Daerah Kota Depok Nomor 15 Tahun 2013 Perspektif Siyasah Dusturiyah - Izzati Muadzah Al Adawiyah; Ridwan Eko Prasetyo; Yana Sutiana (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2027)
This study examines the implementation of Article 19 of Depok City Regional Regulation Number 15 of 2013 on the 12-year compulsory education policy within the framework of Siyasah Dusturiyah. Employing a qualitative juridical-empirical approach combined with descriptive-analytical methods, the study finds that data verification, equivalency education, financial assistance, and the free private school program have contributed to a decline in school dropout rates, notwithstanding persistent constraints related to data integration and school capacity. The analysis indicates that these policies are aligned with the principles of amanah, justice, and ḥifẓ al-‘aql; however, their implementation still requires strengthened data governance and more equitable access to education.